Cigarette smoking induces atrial fibrosis in humans via nicotine. Issue 9 (29th March 2007) - Goette, Andreas; Lendeckel, Uwe; Kuchenbecker, Anja; Bukowska, Alicja; Peters, Brigitte; Klein, Helmut U; Huth, Christof; Röcken, Christoph
Abstract : Background: Cigarette smoking (CS) promotes endothelial dysfunction and atherosclerosis in the vascular bed. The impact of smoking on atrial myocardium is not defined in humans. Objective: To determine the effect of CS on the development of interstitial fibrosis in atrial myocardium. Design: Case–control study. Patients: 95 patients (46 smokers and 49 non-smokers) undergoing coronary artery bypass grafting (CABG). Main outcome measures: Amount of atrial fibrosis, collagen I, III and IV expression pattern, and quantitative reverse transcriptase-PCR. Occurrence of postoperative atrial fibrillation (AF). Results: In the study population, patient age correlated significantly with the amount of atrial fibrosis (r = 0.18; p<0.05). Nicotine misuse (pack years) was identified as the only factor related to atrial fibrosis in smokers (r = 0.311; p<0.05). The amount of fibrosis was higher in patients with postoperative AF (22.9% (6.2%) vs. 27.0% (8.2%); p<0.05). To show a causal relationship between CS and atrial fibrosis, atrial tissue slices from non-smokers (n = 8) were cultured in the presence of nicotine base (185 and 740 nmol/l). Nicotine base induced mRNA expression of collagen III (up to 10-fold) in a concentration-dependent manner resembling the immunohistological collagen expression pattern observed in CS. Conclusion: CS contributes to the development of atrial fibrosis via nicotine. Atrial fibrosis by itself has been shown to provide an arrhythmogenic substrate, which may increase the likelihood of the occurrence of atrial arrhythmias, including postoperative AF.